K(+)/Na(+)-triggered bioluminescence in the oceanic squid Symplectoteuthis oualaniensis - Tsuji, Frederick I. (1981)
A distinctive type of luminescent system present in the large dorsal luminous organ of the oceanic squid Symplectoteuthis oualaniensis is described. The organ produces an intense blue flash of light followed by a rapid decay in light intensity. Luminescence originates from numerous oval granules present in the luminous organ. The essential light-emitting components are membrane bound. Intact granules or washed homogenates of the granules are triggered to emit light by monovalent cations such as, in decreasing order of effectiveness, potassium, rubidium, sodium, cesium, ammonium, and lithium. Calcium, magnesium, and strontium ions do not trigger light emission. Analysis of the kinetics of the decay of light intensity suggests that two light-emitting components are involved, one decaying faster than the other. The light-emitting reaction has an absolute requirement for molecular oxygen. The optimum KCl or NaCl concentration is ≈0.6 M and the optimum pH is ≈7.8. A free sulfhydryl group is essential for activity.